Covid-19 Impact on Banking Sector: Case of Latvia - Aija PILVERE-JAVORSKA; Baiba RIVZA (Communications of International Proceedings, 2020)
Covid-19 pandemic first wave took place in second quarter 2020 in Latvia. Rapid reaction from the government imposing restrictions, resulted in medical “success” with few causalities. Impact on the economy is still to be evaluated, while the main indicators and predictions are in, Latvia is expected to face the largest GDP contraction among Baltic States. Banking is one of the main sectors securing funding lifeline to the companies, in order to produce goods and services, provide employment, thus to create value added for economy. The aim of the research is to assess the Covid-19 pandemic first wave impact on how banks operate and what is funding availability to enhance economic recovery possibilities in Latvia. Authors discovered that already after 2008 recession bank lending had an overall trend to decrease in Latvia, thus reducing available funding to the companies and households for recovery. Bank business model has changed already before Covid-19 pandemic, especially in the light of restructuring of banking sector by supervisory institutions. Covid-19 impact in banking sector has been to whom banks lend money, there are significant increase in lending to government, holding and lending money to Central Bank and other monetary financial institutions, while we saw even further reduction of lending to companies. Overall major banks’ profits have seen a drop in Q22020, but they remained profitable, with exception one of the major banks experienced significant losses.
Keywords: Covid-19; banking sector; impact analysis; Latvia.